Ademetionine treatment cost analysis of patients with intrahepatic cholestasis and non-alcoholic fatty disease - M. V. Zhuravleva; G. V. Kukushkin; E. V. Luchinina; T. V. Shelekhova; T. R. Kameneva; E. V. Kuznetsova; E. A. Luchinin (Качественная клиническая практика, 2022)
Relevance. Ademetionine is a hepatoprotective drug, is included in the  draft Russian clinical guidelines for the  diagnosis and treatment of non-alcoholic fatty liver disease (NAFLD) and in the  clinical guidelines for treating intrahepatic cholestasis (ITH), the cost analysis of treating patients with ITH and NAFLD is topical. Aim. The cost analysis of treatment with ademetionine for ITH and NAFLD in the Russian Federation. Methods. This clinical and economic analysis was conducted in accordance with the requirements of GOST R 57525–2017 and the methodological recommendations of the  Center for Expertise and Quality Control of Medical Care. At the  first stage, to determine the  structure and number of costs, a review of legal acts and publications on the  pharmacoeconomic analysis of clinical situations and drugs of interest in the  e-Library and ConsultantPlus databases was carried out. The  source of prices for medical services was the tariffs of the compulsory medical insurance system and data from the tariff agreement in Moscow within the framework of the compulsory medical insurance system, and in the absence of tariffs, the  prices for paid medical services. Prices for drugs were obtained from an open source — the  Russian Pharmaceutical Portal (Pharmindex.rf). In the  absence of data on the  cost structure, a survey of physicians conducted through a questionnaire. Results. Because of the literature review, 34 publications were found in the  e-Library database on the use of ademetionine in NAFLD and ITH. Additionally, outside the scope of the literature review, a study was found in 2011, which provides a comparative clinical and economic analysis of the  use of ademetionine (Heptral®) and essential phospholipids (Essentiale) in alcoholic liver damage and in infectious hepatitis. A review of legal acts in the  ConsultantPlus database initially identified 93 documents, of which 25 turned out to be irrelevant to the current purpose of the study, that is, they didn’t allow analyzing the costs of ademetionine therapy. Of the 20 identified standards of medical care, only 2 are devoted to diseases of the liver and biliary tract. Because of the analysis, it was revealed that the cost per case of NAFLD treatment in a round-the-clock hospital amounted to 24.6 thousand rubles; in a day hospital, the  cost per case of both NAFLD and ITH in adults amounted to 19.8 thousand rubles each. The average total cost of treating one patient during the year on an outpatient basis for NAFLD amounted to 65.3 thousand rubles, of which only 14.3 thousand rubles. covered by the compulsory medical insurance system, 16.9 thousand rubles outside the compulsory medical insurance system and 34.1 thousand rubles — drug costs. The average total costs for treating one patient during the year on an outpatient basis from ITH amounted to 65.4 thousand rubles, of which 23.9 thousand rubles. covered by the compulsory medical insurance system, 17.6 thousand rubles outside the compulsory medical insurance system and 23.9 thousand rubles — drug costs. Conclusion. Because of the study, the average costs for treating patients with NAFLD and ITH were calculated, which can later be used to conduct other types of pharmacoeconomic analysis.